A revolução dentro da ordem: Brasil e EUA - Silva, Leonardo Barbosa e (Faculdade de Ciências e Letras - Unesp - Araraquara., 2017)
The article tries to analyse the conservative nature in the burgeosy revolution in the USA and in Brazil. However, it aims to gaagainst the perception in the academic circle relation to conservative inners.